Intelligent systems for agriculture in Japan. - Hashimoto, Y. (IEEE Control systems magazine)
The paper presents findings of agriculture research conducted in Japan in three areas: 1) artificial intelligence applications in agriculture and the environments: 2) intelligent environment control for plant production systems; and 3) intelligent robots in agriculture. The latest biosystem derived algorithms are discussed. A finite element inverse technique using a photosynthesis algorithm is described, following by a comparison of neural network (NN) training by the photosynthetic algorithm versus genetic algorithm (GA). Leaf cellular automata are introduced, and their application to optimisation problems is discussed. A decision system consisting of NNs and GAs is applied to the optimisation of plant growth under hydroponics in Japanese plant factories. In this system, the plant growth affected by nutrient concentration is first identified using NNs. Finally, recent developments in intelligent agricultural robots in Japan are introduced